Aaahh!!! real monsters. The complete series [videorecording (DVD)]. - Adler, Charlie, 1956-; Cavanaugh, Christine; Eccles, David (Shout! Factory, 2013)
Meet Ickis, Oblina and Krumm, three young monsters at the "scariest" school you've ever seen! But when they're not learning the best methods of frightening humans from their headmaster, The Gromble, the trio is facing off against a determined monster-hunter named Simon. Can they keep the secrets of the monsters safe while on their crazy adventures?